Is Public Value Realized? A Case Study of the Family Hope Program (PKH) in Joyoboyo Village, Surabaya - Devira Yusufi, Arinda; Fierda Nurany; Bagus Ananda Kurniawan (Faculty of Social and Political Science, 2026)
This research is motivated by the importance of ensuring that the implementation of social assistance programs not only produces economic benefits, but also creates public value that is felt fairly by the community. However, in its implementation, the Family Hope Program (PKH) still faces challenges related to the accuracy of targets and the perception of justice. Therefore, this study aims to analyze public value in the implementation of PKH in Joyoboyo Village, Sawunggaling Village, Surabaya City. This study uses a qualitative method with a descriptive approach. Data was collected through in-depth interviews with PKH coordinators, Ministry of Social Affairs surveyors, regional apparatus, PKH recipients and non-recipients, and supported by documentation. Data analysis was carried out using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that PKH in Joyoboyo Village has created public value through improving community welfare, especially in meeting basic needs, access to education, and health services, as well as encouraging behavior change for the better. The legitimacy of the program is strong because it is supported by clear regulations and public trust in DTSN-based mechanisms, while operational capacity is also adequate through companion competencies, effective coordination, and responsive services. However, the resulting public value is still partial due to the problem of accuracy of the target and the perception of injustice. This research contributes to enriching the study of public value by showing that the success of social assistance programs is not only determined by the benefits generated, but also by the accuracy of the data, social legitimacy, and integrated operational capacity. The implications of this research emphasize the importance of continuous data updating, increasing transparency, and strengthening public participation to realize more inclusive and sustainable public value.